2002
DOI: 10.1093/emboj/21.7.1661
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of endophilin A in synaptic vesicle budding at the Drosophila neuromuscular junction

Abstract: We characterized Drosophila endophilin A (D-endoA), and generated and analysed D-endoA mutants. Like its mammalian homologue, D-endoA exhibits lysophosphatidic acid acyl transferase activity and contains a functional SH3 domain. D-endoA is recruited to the sites of endocytosis, as revealed by immunocytochemistry of the neuromuscular junction (NMJ) of mutant L3 larvae carrying the temperature-sensitive allele of dynamin, shibire. D-endoA null mutants show severe defects in motility and die at the early L2 larva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 19 publications
4
102
1
Order By: Relevance
“…It has been reported that endophilin A1 is mainly expressed at the presynaptic site [11] and plays a critical role in synaptic vesicle recycling via regulation of clathrin-mediated endocytosis [14][15][16][17][18][19][20][21]. However, our previous study has demonstrated that endophilin A1 interacts with retrolinkin in dendrites of mammalian central nervous system neurons and mediates the endocytic trafficking and signaling of the BDNF-TrkB ligand-receptor complex during dendrite outgrowth [22].…”
Section: Endophilin A1 Localizes In Dendritic Spinesmentioning
confidence: 90%
See 1 more Smart Citation
“…It has been reported that endophilin A1 is mainly expressed at the presynaptic site [11] and plays a critical role in synaptic vesicle recycling via regulation of clathrin-mediated endocytosis [14][15][16][17][18][19][20][21]. However, our previous study has demonstrated that endophilin A1 interacts with retrolinkin in dendrites of mammalian central nervous system neurons and mediates the endocytic trafficking and signaling of the BDNF-TrkB ligand-receptor complex during dendrite outgrowth [22].…”
Section: Endophilin A1 Localizes In Dendritic Spinesmentioning
confidence: 90%
“…It was reported recently that although single knockout mice appear normal and fertile, double knockout of endophilin A1 and A2 or knockout of all three endophilins in mouse causes accumulation of clathrin-coated vesicles at the presynaptic site, indicating that they play redundant functions in vesicle uncoating after membrane fission [13]. Although a critical role of endophilin A1 in regulating synaptic vesicle endocytosis at the presynaptic terminal has been well established [14][15][16][17][18][19][20][21], its function at the postsynaptic site remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, mutant Drosophila larvae lacking endophilin failed to take up FM1-43 dye in synaptic boutons, indicating an inability to retrieve synaptic membrane (13,14). Based on these findings and the similarity of Endo3 to Endo1 and Endo2, we initially expected that Endo3 would activate the endocytosis of synaptic vesicles.…”
Section: Promotion Of Dopamine-induced Differentiation Of An Olfactormentioning
confidence: 98%
“…This membrane invagination is thought to require localized alterations in phospholipid composition leading to changes in membrane curvature. One protein that may play an important role in altering membrane curvature is Endophilin, a lysophosphatidic acid acyltransferase that is required for the endocytosis of synaptic vesicles (Schmidt et al 1999;Guichet et al 2002;Verstreken et al 2002). Once the inward budding of the membrane is complete, interactions between AP-2 and the GTPase Dynamin allows fission of the forming vesicle from the membrane (Wang et al 1995;Ringstad et al 1997).…”
Section: Internalization Of Signaling Molecules From the Surfacementioning
confidence: 99%